Insuficiencia de un régimen normativo municipal para controlar la contaminación y degradación del medio ambiente a través de un adecuado tratamiento de los desechos sólidos - GODOY ORTEGA, BAYRON STALIN (2010)
The present investigation approaches the artificial problem that affects all the Ecuadorian citizens in what refers with the environmental and partnerenvironmental damages caused by the solid wastes that are heady to the atmosphere, for that that at the present time the contamination and degradation of the Environment is a serious problem, due to the absence of handling programs, especially of the solid residuals, and these in turn don't receive an appropriate treatment on the part of the Autonomous Decentralized Governments, causing serious damages to the nature. In this context it could be defined to the environmental contamination as a crime, against the health and the life, without it levies the behavior of the residents and society in general causing or authors of the environmental damage, affect juridical fundamental goods protected by the Constitution of the Republic of Ecuador and the Environmental Legislation, forcing the rights therefore and régime of the Good one to Live, added this the lack of mechanisms that you/they establish immediate sanctions, without many procedures and juridical ties that should be guided by the State by means of the punitive attributed organisms of social control. It is for that reason that the present thesis implies a deep analysis of the normative one of the Constitution of the Republic, Law of Environmental Management and Municipal Organic Law of Régime that protect the environmental rights of people, reason why it is necessary to treat this investigation topic since in our county of Loja, in the cantons it is evident the environmental contamination generated by the solid wastes, and people that act, some for ignorance of the laws and of the sanctions that he/she brings I get the environmental contamination, and the lack of control organisms and sanctions or in its case the inadequacy of a normative municipal régime, so that these people think and reflect when they want to make an infraction to the environment that due to these environmental problems, it is considered indispensable the implementation of integral programs of handling, reduction, reciclaje and treatment of the solid residuals, with alternative technologies environmentally sustainable and sustainable of the ecosystems, on the part of the Autonomous Decentralized Governments. Also in the present investigation he/she was carried out an itemized study of the problem outlined so much in the doctrinal, juridical, analytic and critical aspects.